2006
DOI: 10.1002/chem.200500415
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Threading Synthesis of Isomer‐Free [2]Rotaxanes

Abstract: The threading of an alpha-cyclodextrin (alpha-CyD) by an unsymmetrical dumbbell generally results in two isomeric [2]rotaxanes differing in the orientation of the alpha-CyD. In this work, two methods have been developed for the unidirectionally threading an alpha-CyD to obtain isomer-free [2]rotaxanes. These methods use the Suzuki coupling of a boronic acid derivative and a halide in aqueous alkaline solution. The conformations of the two unidirectional [2]rotaxanes-R3 and R4 were determined by 2D 1H ROESY NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 63 publications
2
39
0
1
Order By: Relevance
“…For synthesis of unidirectional [2]rotaxanes the Suzuki coupling of iodides and boronic acid derivatives in an aqueous a-CD solution has been performed. The obtained unidirectional [2]rotaxanes 35-38 upon irradiation show E/Z photoisomerization and shuttling motion of the CD ring [73].…”
Section: Shuttling Of a Ring In CD Rotaxanesmentioning
confidence: 99%
“…For synthesis of unidirectional [2]rotaxanes the Suzuki coupling of iodides and boronic acid derivatives in an aqueous a-CD solution has been performed. The obtained unidirectional [2]rotaxanes 35-38 upon irradiation show E/Z photoisomerization and shuttling motion of the CD ring [73].…”
Section: Shuttling Of a Ring In CD Rotaxanesmentioning
confidence: 99%
“…Park and Song have prepared the two orientational isomers of a a-CD [2]rotaxane with carbazole and bulky viologen stoppers [30]. The assemblies of a-CD [2]-and [3]rotaxanes with asymmetric threads that exhibit only one orientational isomer have also been prepared, by the research groups of Anderson [31][32][33], Tian [34,35] and Park [36,37]. Park has recently re-evaluated the rate and equilibrium constants for the formations and dissociations of CD inclusion complexes to incorporate bidirectional inclusion pathways involving orientational isomers [38].…”
Section: Introductionmentioning
confidence: 97%
“…23 Seok Seo et al discussed the fluorescence resonance energy transfer efficiency between GO and Cy3.5 dye by controlling the donor-acceptor distance using double-stranded DNA and demonstrated that the GO serves as an acceptor rather than a donor in this FRET system. 24 Rotaxane, a typical interlocked supramolecular system, 25-26 is described as a molecular system in which the macrocycle interlocks with a dumbbell structure by noncovalent interaction, [27][28][29] i.e., two bulky stoppers at the end of the axle are prepared to prevent dethreading of the cyclic component. [30][31] Because of their unique structural architectures, some supramolecular rotaxanes display increasing potential for use in applications such as molecular switches, molecular logic gates, molecular wires, and information storage.…”
Section: Introductionmentioning
confidence: 99%